2004
DOI: 10.1016/s0887-8994(03)00413-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-brain antibodies in PANDAS versus uncomplicated streptococcal infection

Abstract: The objective of this study was to assess brain involvement through the presence of antineuronal antibodies in Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcus (PANDAS) and in uncomplicated active Group A streptococcal infection. We compared serum antibrain antibody to human basal ganglia sections assessed by indirect tissue immunofluorescence in two groups: a PANDAS group, comprised of 22 patients (mean age 10.1 years; 20 male, 2 female) who met strict National Institutes of Menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 10 publications
4
84
0
2
Order By: Relevance
“…Most studies involving antineuronal antibodies have been in those patients with tics with Streptococcus-related symptoms. There were very few studies which have considered antineuronal antibodies in patients with Tourette's syndrome, the clinical symptoms of which do not correlate with streptococcal infection.The most recent study compared the PANDA group and the uncomplicated active Group A streptococcal infection children and found that the presence of antibrain antibody could not be explained merely by the history of GABHS infection [32]. The sera from clinical OCD cases showed antibodies directed against caudate and putamen at a rate significantly higher than that of clinical controls, providing evidence of basal ganglia involvement in OCS without Streptococcus infection [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies involving antineuronal antibodies have been in those patients with tics with Streptococcus-related symptoms. There were very few studies which have considered antineuronal antibodies in patients with Tourette's syndrome, the clinical symptoms of which do not correlate with streptococcal infection.The most recent study compared the PANDA group and the uncomplicated active Group A streptococcal infection children and found that the presence of antibrain antibody could not be explained merely by the history of GABHS infection [32]. The sera from clinical OCD cases showed antibodies directed against caudate and putamen at a rate significantly higher than that of clinical controls, providing evidence of basal ganglia involvement in OCS without Streptococcus infection [4].…”
Section: Discussionmentioning
confidence: 99%
“…The striata were carefully dissected out under a dissecting microscope, according to the procedures described by Smart and Sturrock [32,35]. They were then placed into another dish containing ice-cold phosphate-buffered saline (PBS) to thoroughly remove blood vessels and membranes from the striatal tissues.…”
Section: Primary Neuronal Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms by which these autoantibodies cause clinical manifestations in central nervous system (CNS) diseases include direct stimulation or blockade of receptors in the basal ganglia, or immune complexes promoting inflammation of these brain regions (Giedd et al 1996(Giedd et al , 2000. Antineuronal antibody binding to basal ganglia tissue was found in both patients with PANDAS (Pavone et al 2004) and patients with ADHD (Sanchez-Carpintero et al 2009), whereas in SC patients, increased antineuronal antibody binding to basal ganglia tissue correlates with symptom severity (Church et al 2002;Husby et al 1976;Kotby et al 1998). More recently, monoclonal antibodies to N-acetyl-beta-d-glucosamine, the dominant epitope of GAS carbohydrate, and lysoganglioside GM1, a neuronal cell-surface molecule, have been cloned from children with SC (Kirvan et al 2003(Kirvan et al , 2006.…”
Section: Serologic and Prospective Studiesmentioning
confidence: 99%
“…Investigators are now finding antineuronal antibodies among the PANDAS subgroup that are specific to the basal ganglia as well. 75,76 Preliminary results suggest that an antineuronal antibody found in SC patients that stimulates neuronal transduction may also be present in a group of PANDAS subjects (Kirvan, 2003 personal communication).…”
Section: Pathogenesis Of Pandasmentioning
confidence: 99%